Annotated bird sighting list for summer 1999 compiled by Rob Thelen - Thelen, Robet al (1999)
An annotated list of birds sighted by Rob Thelen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1999. Epson - sheet feed